Gender Diversity, Firm Age, and Intellectual Capital Disclosure: A Multi-Country Study of ASEAN Banks - Wandira, Nabila Ayu; Suzan, Leny (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
Intellectual capital disclosure reflects how firms communicate information about human, structural, and relational capital, which is essential in knowledge-intensive sectors such as banking. This study provides a novel cross-country analysis of how board gender diversity and firm maturity influence intellectual capital disclosure in ASEAN banking markets, positioning profitability as a governance-conditioned control variable. Using panel data from 52 listed banks during 2019–2023, the study employs descriptive statistics and panel regression analysis. Firm age is measured by years since listing, and gender diversity is proxied by the proportion of female directors on the board. The findings show that firm age does not significantly affect intellectual capital disclosure, whereas gender diversity has a positive and significant impact. Profitability strengthens the explanatory power of the model. The results imply that enhancing board gender diversity may serve as an effective governance mechanism to improve transparency in intangible asset reporting within emerging financial markets.